Рrecedent texts in the mass media (Eurasian Journal of Philology Science and Education, 2016)
In article the рrecedent texts used in journalistic style are considered. They express the cultural features of linguocultural community, appeal to the background knowledge, bring expressivity, estimation in the text, and stimulate the reader’s interest. Sources of precedent texts can be literature, language, cinema, history, politics, etc. Efficiency of their use is is conditioned by their knowableness. The reasons of the widespread use of precedent texts in today’s media, both in the titles and within the journalistic text are find out. The special attention is paid to the causes and characteristics of the use of precedent texts in the headlines. There a wide variety of applicable precedent texts and functions. Examples of structural and semantic transformations precedent texts in the language of the newspaper are given.
Keywords: precedent texts; mass media; background knowledge; functions of precedent text.